Actual Texts, Possible Meanings: The Uses of Poetry and the Subjunctification of Experience. Issue 4 (1st October 2016) - Green, Andrew; Ellis, Viv; Simecek, Karen
Abstract: Jerome Bruner's experiment over 30 years ago suggested that imaginative literature had greater affordances for the 'subjunctification' of experience by those who heard it read aloud than did transactional prose such as a news article. By 'subjunctification', Bruner meant the capacity to use the resource (the short story, for example) to transform one's experience of the world, to render understanding in more complex ways and to do more than get things done as they have always been done. This paper reports on a small-scale replication of the experiment that sought to measure differences in the affordances of poetry being read aloud compared to hearing a short story or a news article.